STUDI AWAL RESPON DINAMIS BERDASARKAN PENGUKURAN MIKROTREMOR DI BENDUNGAN KARANGKATES MALANG - Philips Bramantia Mudamakin; Ariska Rudiyanto; Supriyanto Rohadi; Rizki Amalia (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Based on earthquake data over the past 29 years, there were 191 events were felt in the region of Karangkates, Malang. The aim of this study is to determine the trend of dynamic response of the frequency for Karangkates Dam, Malang. This study uses primary data, perform data retrieval directly at the Karangkates Dam, Malang. The instruments named Portable Digital Seismograph type Taide TDL-303S and Digital Seismograph type Taide TDV-23S was used for the microtremor measurements. Microtremors data were analyzed using Horizontal to Vertical Spectral Ratio (HVSR) and comparison of the spectrum of each component by comparing the trend of dynamic response of the frequency. The results showed that the average trend of the frequency each component changed significantly following the activity of water in the Karangkates Dam, Malang. The highest average value for the amplitude spectrum of each component is the vertical component (Z) = 2841.39 at frequency 4.2076 Hz, the East-West component (EW) = 3656.82 at frequency 5.3515 Hz, and the North-South component (NS) = 2223.97 at frequency 5.1708 Hz respectively.Keywords: trend of dynamic response, microtremor, spectrum, frequency.